Description of Stress on Parents in Caring for Children with Intellectual Disabilities - Niara, Kinaya Vathia Zalva; Rukmasari, Ema Arum; Sriati, Aat (Indonesian Journal of Global Health Research, 2024)
Children with intellectual disabilities have limitations in cognitive functions and adaptive behavior. This makes parents who have children with intellectual disabilities face many problems like social isolation, community stigma, loss of hope, and unrealistic expectations regarding children’s conditions. This research aims to determine the stress on parents in caring for children with intellectual disabilities. This research uses quantitative descriptive methods. The sampling strategy used total sampling and obtained sample 74 of parents who had children with intellectual disabilities without comorbidities and whose children attend at the SLB Negeri Cileunyi. Data were collected using the parenting stress scale questionnaire. Data analysis was conducted using univariate analysis with cross-tabulation. The results of this research are that the majority of parents of children with intellectual disabilities experience low levels of parenting stress. Based on the characteristics of respondents, higher levels of parenting stress were experienced by mothers aged between 45-65 years, with secondary education, not working, and with a monthly family income below the minimum wage. Meanwhile, based on children's characteristics, parents who have higher levels of parenting stress have daughters aged between 12-21 years with moderate intellectual disabilities.